Study of Right to Education - Bishnoi, Monika (Universal Research Reports, 2018)
Free and compulsory education for all children aged six to fourteen years was enshrined in the “Constitution of India by the Constitution (Eighty-sixth Amendment) Act, 2002, which added Article 21-A to the Constitution. As outlined in Article 21-A, every child has the right to a free and compulsory primary education in a school that meets certain necessary requirements and norms under the Right of Children to Free and Compulsory Education (RTE) Act, 2009.